Residential location, commuting and non-work travel in two urban areas of different size and with different center structures. (February 2019) - Næss, Petter; Strand, Arvid; Wolday, Fitwi; Stefansdottir, Harpa
Highlights: This paper presents results from a study of commuting and non-work travel in a large, monocentric and a smaller, polycentric city region. The study combines a questionnaire survey with qualitative interviews and includes cross-sectional as well as longitudinal analyses. In both regions and for commuting as well as non-work trips, inner-city dwellers make a higher share of non-motorized trips and a lower share by car. Commuting distances depend heavily on proximity to each region's main job concentration: inner Oslo and a suburban business park in Stavanger. Local built environment characteristics play a greater role for trip distances to non-work destinations, particularly in Oslo. Abstract: There is an extensive literature on relationships between the built environment and travel, but the vast majority of such studies rely solely on statistical analyses of available travel survey data, with limited possibilities for demonstrating causality. This article presents findings from a methodologically novel study drawing on a combination of a tailor-made questionnaire survey and in-depth qualitative interviews, including cross-sectional as well as longitudinal analyses. Our mixed-methods approach offers stronger evidence of causal influences than in most previous studies on the built environment and travel. We illuminate such relationships in two metropolitan areas differing considerably in their size and urban structure: the relatively monocentric Norwegian capital Oslo and the smaller, predominantly polycentric Stavanger area. The study encompasses travel distances and modes for both commuting and intra-metropolitan non-work purposes. The paper thus offers a comparison of the influences of built environment characteristics on travel across metropolitan contexts as well as for different travel purposes.